Hijrah and Islamic Movement in Social Media: A Social Movement Study of Anti-Dating Movement #IndonesiaTanpaPacaran - Sari, Trie Yunita; Husein, Fatimah; Noviani, Ratna (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This article examines a flourishing Islamic youth movement in Indonesia, #IndonesiaTanpaPacaran or Indonesia without Dating. This movement calls for hijrah (literally means an action of moving to another place) from Western dating habits to ta'aruf or an Islamic practice of getting married without dating among the Muslim millennial. This article aims to explain the emergence of this movement. Drawing approach from social movement theory, the writer argues that this movement is culturally embedded since piety, religious commodification and political resistance against existing political nuance are overshadowed the emergence of this anti-dating movement. It is found out that this movement is an offshoot of banned Islamic organization Hizbut Tahrir Indonesia (HTI) that continuously struggles to revive the past transnational rule of khalifah (caliphate) in Indonesia. Consequently, the concept of hijrah in social media campaign does not only to promote Islamic lifestyle like ta'aruf but also to promote caliphate as an alternative to secular democracy. This study is presented given the fact that the research on Islamic youth movement in social media is still lack of attention, despite the so-called hijrah movement is legion and may strategically important to make social change through the use of social media.